The influence of brand image and promotion on customer loyalty - Nasution, Ridwan (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2025)
Brand image and promotion are factors that can be considered by consumers in decision making. This research method uses a quantitative approach. The sample of this research is customers at Mie Atok Rantauprapat. The results of the study show that brand image and promotion affect customer loyalty.